2010
DOI: 10.1111/j.1399-0012.2010.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of fatigue and sleep quality before and after kidney transplantation

Abstract: Fatigue and sleep disturbances are common problems for adults with chronic kidney disease or end-stage renal disease. However, these issues have not been examined much in the context of kidney transplantation (KTx). This study characterizes these outcomes in the KTx population and examines their association with psychological functioning and quality of life (QOL). A cross-sectional cohort of 100 wait-listed pre-KTx and 100 post-KTx patients at one transplant center in the United States completed validated fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 46 publications
9
48
1
7
Order By: Relevance
“…Depressive symptoms and sleeping problems were most strongly related to severe fatigue, while the other assessed factors were no longer significant in multivariate analysis. Our finding that severe fatigue was related to depressive symptoms, sleeping problems and also overweight is in accordance with the study of Rodrigue et al [6]. The prevalence of obesity in our sample (13%) seems to lie in the same range as the Dutch population (11% in 2011) [41].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Depressive symptoms and sleeping problems were most strongly related to severe fatigue, while the other assessed factors were no longer significant in multivariate analysis. Our finding that severe fatigue was related to depressive symptoms, sleeping problems and also overweight is in accordance with the study of Rodrigue et al [6]. The prevalence of obesity in our sample (13%) seems to lie in the same range as the Dutch population (11% in 2011) [41].…”
Section: Discussionsupporting
confidence: 92%
“…We found that as many as 39% of the recipients were severely fatigued compared with 22% of the sex-and age-matched population-based control group. Our results revealed a lower percentage of severe fatigue than previously found in comparison to healthy individuals [6]. The discrepancy could be explained by the fact that a different questionnaire was used, and that the chosen cut-off score was determined with a different method.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The combination of reduced activity and increased fatigue can lead to increased idle time in bed and is likely related to mood disturbance. 20,22 Insomnia is maintained by perpetuating factors, which may include changes individuals make in their sleep/wake schedules or daytime behaviors (e.g., stimulant use and napping) as they attempt to compensate for sleeping poorly. 20 Specifically, daytime naps may disrupt the sleep homeostat (drive for sleep that increases the longer one is awake) by meeting some of the sleep drive that typically builds during the day.…”
Section: Scientific Investigationsmentioning
confidence: 99%
“…또한 우울 (Kalender, Ozdemir, Dervisoglu, & Ozdemir, 2007), 불안 (Tong et al, 2009), 피로 (Rodrigue et al, 2011), 수면 장애 (Cohen, Patel, Khetpal, Peterson, & Kimmel, 2007)와 같은 생행동적 요인이 삶의 질에 부정적인 영향 을 미치는 것으로 보고되었으며 (Wood, Klebba, & Miller, 2000), 사회 적 지지 또한 만성 신부전 환자의 삶의 질에 직접적 (Cohen et al) 또 는 간접적으로 영향을 주는 것으로 보고되었다 (Hoth, Christensen, Ehlers, Raichle, & Lawto, 2007). 영양학적, 신체적 요인은 수면장애 (Cohen et al), 우울 (Kohatsu, 2005) …”
Section: 투석 전 만성 신부전 환자의 삶의 질에 영향을 주는 요인으로 영unclassified